An objective analysis of composite free flap donor site morbidity in head and neck surgery: Prospective series. Issue 2 (27th November 2022) - Russell, Joshua; Volker, Glen; McGarvey, Declan; Sharpe, Catherine; Breik, Omar; Borgna, Scott C.; Pateman, Kelsey; Batstone, Martin
Abstract: Background: A poor evidence basis exists regarding the objective donor site morbidity associated with osseous free flap harvest. This study prospectively assessed the objective donor site morbidity associated with osseous free flap harvest for the fibula, scapula, and iliac crest (DCIA) donor sites. Methods: A single‐site, prospective cohort clinical research study was conducted. Sixty‐four patients were recruited between 2017 and 2021. Patients were assessed using a donor site specific assessment tool pre‐operatively, and again >12 months post‐operatively. Results: There was a significant reduction post‐operatively in assessment tool scores compared to the pre‐operative period for the fibula, scapula and DCIA. Females were more likely to report a greater reduction in Harris Hip Score post‐operatively compared to males. Conclusions: The fibula, scapula, and DCIA donor sites are associated with reduced objective function post‐operatively compared to patient's pre‐operative baseline. The implications are least pronounced for the fibula.